Effectiveness of Zingiberaceae Herbal Extracts from the Hala-Bala Forest for Application in Thai Massage - Thipmanee, Orawan; Waema, Sunee; Samanman, Saluma; Benhawan, Aeesoh (Molekul, 2025)
ABSTRACT. This research aimed to study the efficiency of essential oils extracted from Zingiberaceae herbals that are Etlingera elatior, Zingiber montanum, and Etlingera coccinea, collected from the Hala-Bala forest in Chulabhorn Pattana Village 9, Ban Santisuk 2, Mae Wat Sub-district, Than To and Betong District, Yala Province. The essential oils were extracted using steam distillation and characterized based on their physical and chemical properties, antimicrobial activity, phytochemical composition, and antioxidant activities. The pH values of the essential oils were found to be 6.1, 4.9, and 6.2, respectively. Heavy metal analysis of the essential oils, conducted using a flame atomic absorption spectrophotometer, revealed no contamination with lead, chromium, manganese, and cadmium. In antimicrobial activity test against three bacterial strains— Staphylococcus aureus, Bacillus spp., and Escherichia coli—the essential oils of E. elatior and Z. montanum demonstrated inhibitory effects against all three strains, with inhibition zones ​​of 12.3±0.28, 10.7±1.06, and 11.2±1.01 mm for E. elatior and 22.1±1.25, 26.0±0.70, and 18.5±0.70 mm for Z. montanum. Meanwhile, the essential oil of E. coccinea inhibited S. aureus and E. coli with inhibition zones ​​of 20.5±0.70 and 13.2±0.35 mm, respectively. Preliminary phytochemical analysis was performed using high-performance thin-layer chromatography (HPTLC), and antioxidant activity evaluated using three assays: DPPH radical scavenging activity (DPPH assay), ABTS free radical bleaching (ABTS assay), and ferric reduction of antioxidant power (FRAP assay). The results confirmed that all three essential oils exhibited antioxidant activity, and the phytochemical screening detected flavonoids, diterpenes, and anthraquinones. This research highlights the potential of the essential oils for developing Thai massage health products, particularly in the form of massage oils infused with natural extracts and local herbs. Volunteer satisfaction assessments conducted at the Thai Traditional Medicine Learning Center, Yala Rajabhat University, Yala Province, Thailand, indicated a high to the highest level of satisfaction. This was attributed to the oils' natural composition, low toxicity, and high effectiveness. Keywords: Antibacterial, Antioxidant, Etlingera elatior, Essential oil, Etlingera coccinea, Phytochemical, Zingiber montanum